2020
DOI: 10.1051/0004-6361/202038953
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the past and future activity of the Halleyid meteor showers

Abstract: Context. We present a new numerical model of the η-Aquariid and Orionid meteor showers. Aims. The model investigates the origin, variability, and age of the η-Aquariid and Orionid apparitions from 1985 to the present day in order to forecast their activity over the next several decades. Methods. Through the numerical integration of millions of simulated meteoroids and a custom-made particle weighting scheme, we model the characteristics of every η-Aquariid and Orionid apparition between 1985 and 2050. The mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…This opens up the possibility that some of these meteoroid streams may be elliptical in cross-section. This is supported by other studies: for instance, both observations (Vida 2020) and models (Egal et al 2020) of the Orionid meteor shower indicate a complex radiant structure. An apparently asymmetric Orionid radiant distribution is also presented in Fig.…”
Section: Discussionsupporting
confidence: 87%
“…This opens up the possibility that some of these meteoroid streams may be elliptical in cross-section. This is supported by other studies: for instance, both observations (Vida 2020) and models (Egal et al 2020) of the Orionid meteor shower indicate a complex radiant structure. An apparently asymmetric Orionid radiant distribution is also presented in Fig.…”
Section: Discussionsupporting
confidence: 87%
“…In that study, the GMN contributed the most observed trajectories and the GMN mean orbit was in agreement with orbits reported by other networks. Finally, Egal et al (2020) performed dynamical simulations of the Orionids and the 𝜂-Aquariids, and shown that the radiants observed by the GMN were a good match to their simulations.…”
Section: Overview Of Current Statusmentioning
confidence: 85%
“…Characterization of the absolute flux, variability and particle ★ E-mail: dvida@uwo.ca distribution within streams can therefore provide unique insights into parent body physical properties and evolution (e.g. Egal et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Another potential source of error might be the power law assumption. For example, using a numerical model of meteoroid ejection from comet 1P/Halley, Egal et al (2020) predicted that Orionid meteoroids arriving at the Earth should have a mass distribution which follows a broken power law, notably with several sharp slope changes around 1 mm sizes.…”
Section: Scaling the Flux To A Target Limiting Magnitude Or Massmentioning
confidence: 99%